DYNAMICS OF SOCIAL AND PERSONAL OPTIMISM IN THE CONTEXT OF SOCIETY'S IMPROVEMENT - Abilov Ural Muradovich (Western European Studies, 2025)
Optimism is one of the main determinants of the historical process: The ability to understand the meaning and significance of various actions, To consciously select them, It influences the feeling of one's place in society.
Keywords: Optimism; determinants; significance